Macro Coffee Roastery Promotions using Social Media - Ulfah Setia; Teguh Gunawan Setyabudi (Journal of Business and Management Review, 2021)
The company's sales target can be achieved through ongoing promotional activities. Sales promotion can be done through various media, one of which is social media. Social media is currently a profitable means of promotion because many people in this era use social media. Social media is a necessity along with the development of information technology. This study aims to determine the sales promotion of coffee companies using social media (Facebook, Instagram, and Twitter). Makro Coffee Roastery is a coffee company located in Sumbersari District, Jember Regency. Makro Coffee Roastery processes raw coffee beans into coffee grounds. The types of coffee sold include arabica, liberica, and robusta. Products sold are coffee in the form of coffee beans and powder. Information on research data was collected through observation of social media accounts and interviews with company management. The results showed that the social media (Facebook, Instagram, and Twitter) of the Macro Coffee Roastery account as a media for company promotion and drive the achievement of planned sales. Company sales through social media have increased quite significantly and are considered effective as a way of introducing products to consumers. Other social media need to be used as an effort to increase sales of Macro Coffee Roastery.